Exaggerated risk perception of asbestos-related diseases: commentary - S. V. Jargin (Сибирский научный медицинский журнал, 2023)
Health risks from asbestos have been evaluated on the basis of professional histories from remote past, when exposures at workplaces were greater than today. The linear no-threshold model has been applied, although its relevance has not been demonstrated. Fibers are often found in the lungs and pleura at post mortem examinations. The fnding of fbers does not prove that a disease was caused by asbestos. It can be reasonably assumed that targeted search for mesothelioma and other asbestos-related diseases in exposed people resulted in increased detection rate. Histological and immunochemical characteristics of malignant mesothelioma partly overlap with other cancers, which may contribute to overdiagnosis in exposed populations. Amphibole asbestos is more toxic than chrysotile but there are discrepancies between experimental and epidemiological data. The promising way to obtain reliable information is lifelong animal experiments. Asbestos bans applied in some countries are excessive and should be reconsidered on the basis of independent research. It can be reasonably assumed that non-use of asbestos-containing brakes, freproofng, and insulation increases the harm from fres, armed conﬂicts and trafc accidents.